PENERAPAN METODE SUKU KATA (SYLLABIC METHOD) BERBANTUAN APLIKASI MARBEL MEMBACA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Hamidah Mujaddidah; Erna Suwangsih; Neneng Sri Wulan (STKIP Subang, 2023)
The background of this research is due to the student’s unsatisfactory early reading skills. This research was conducted in class I of SD Negeri Cikondang I with a total of 11 students consisting of 7 male and 4 female students. This study aims to determine students’ activity and early reading skills after implementing the syllabic method with the help of the Marbel Membaca Application. The method that was used in this study was Classroom Action Research (CAR). This study found that the syllabic method with the help of Marbel Membaca Application could improve early reading abilities of class I students at SD Negeri Cikondang I. This is seen from the average value of teacher and student activity as well as the importance of students early reading skills in cycle I and II. The average score for student activity in the cycle I was 75 comparing to the cycle II was 87.5 resulting in an increase of 12.5 points. Besides, during the teacher implementation of teacher activities in cycle I the average score was 73.3 whereas in cycle II 93,3 resulting increase of 20 points. In cycle I, students average reading proficiency score was 57.5, while in cycle II, was 78.1, representing a 20.6 point improvement.